The valuable role of renucleation rate in ultrananocrystalline diamond growth - Barbosa, D. C.; Hammer, Peter [UNESP]; Trava-Airoldi, V. J.; Corat, E. J. (Elsevier B.V. Sa, 2012)
This is a comprehensive study of the ultrananocrystalline diamond renucleation rate. The films deposited in a hot-filament chemical vapor deposition system (HFCVD) used an argon rich environment (90 vol.%), known as ideal for ultrananocrystalline diamond deposition. Substrate temperature (750 degrees C), total pressure (30 Tort) argon flow rate (180 seem) were constant in all experiments. Methane concentrations of 0.25, 0.5, 1, 1.5 and 2 vol.% balanced with hydrogen to a total flow rate of 20 sccm. Scanning electron microscopy (SEM) let morphology inspection. Visible-Raman scattering leaded to estimating relative influence of sp(2) bonds. X-ray photoelectron spectroscopy (XPS) measured the chemical bonds distribution. X-ray diffraction assessed crystallinity and diamond renucleation rates. The increase in methane content in the gas mixture promotes morphology changes from micro (faceted), to nano (cauliflower), and to ultrananocrystalline (ballas-like) diamond. It reaches a lamellar graphitic structure at the higher methane concentration. This transition is concurrent with: a decrease of film specific mass, an increase of diamond renucleation rate, an increase of sp(2) phase content, as seen by Raman spectroscopy and, an increase of C-H bond associated with C-C bond, as measured by x-ray photoelectron spectroscopy. Renucleation shows up as a very important process that presents a quadratic correlation with [CH4] in the feed gas. This new result may help bridging MCD, NCD and UNCD into a single understanding of diamond growth. Crown Copyright (C) 2012 Published by Elsevier B.V. All rights reserved.
Keywords: Diamond film; Ultrananocrystalline; Renucleation; Hot filament CVD